Entrepreneurial Behavior and Opportunity Recognition In Global Career Development - Helmy Rahayu; Ratih Purbasari; Margo Purnomo (Entrepreneurship Faculty, Universitas Garut, 2025)
Motivation plays a vital role in fostering entrepreneurial behavior and influencing decisions of career advances in the international arena. The aim of this qualitative study is to understand how aspects of entrepreneurial motivation, namely need for achievement, autonomy, and risk tolerance, influence individuals seeking to explore cross-border professional experiences. Data collection involved semi-structured interviews with a sample of young professionals who have acquired international experience, followed by thematic analysis of transcribed interviews to create an interpretation of the data. From the thematic analysis, five thematic representations emerged, including: entrepreneurial motivation to pursue international opportunities; risk taking and risk perception in the decision-making process; adaptive learning and cross-cultural adaptability; networking and recognition of global opportunities; and merging of entrepreneurial motivation with international career theory. The results suggest the findings indicate that high motivated individuals are hungry for international opportunities, will seek information and resources to pursue their goal, and develop innovative and strategic connections to manage uncertainty. It seems international experience serves as a media/platform for entrepreneurial learning, and for fostering adaptive decision making and recognition of and facilitating opportunity use. Overall, the study demonstrates that entrepreneurial motivation is not limited to creating new ventures but motivates proactive behavior when considering global careers and career advances. From a theoretical contribution, I examined the Theory of Entrepreneurial Motivation, followed by Effectual Theory, in relation to the international career behavior exhibited. I employ practical contributions for organizations to develop workforce capabilities when considering cross-border careers, as well educational institutions in educating students to navigate this arena.